NMJ-related diseases beyond the congenital myasthenic syndromes - Navarro-Martínez, Alejandra; Vicente-García, Cristina; Carvajal, Jaime J. (Frontiers in Cell and Developmental Biology, 2023)
Neuromuscular junctions (NMJs) are a special type of chemical synapse that transmits electrical stimuli from motor neurons (MNs) to their innervating skeletal muscle to induce a motor response. They are an ideal model for the study of synapses, given their manageable size and easy accessibility. Alterations in their morphology or function lead to neuromuscular disorders, such as the congenital myasthenic syndromes, which are caused by mutations in proteins located in the NMJ. In this review, we highlight novel potential candidate genes that may cause or modify NMJs-related pathologies in humans by exploring the phenotypes of hundreds of mouse models available in the literature. We also underscore the fact that NMJs may differ between species, muscles or even sexes. Hence the importance of choosing a good model organism for the study of NMJ-related diseases: only taking into account the specific features of the mammalian NMJ, experimental results would be efficiently translated to the clinic.